2021
DOI: 10.3390/plants10122573
|View full text |Cite
|
Sign up to set email alerts
|

Aegle marmelos Leaf Extract Phytochemical Analysis, Cytotoxicity, In Vitro Antioxidant and Antidiabetic Activities

Abstract: For many years, Aegle marmelos (A. marmelos) has been used medicinally and as a dietary supplement. Despite this, there are minimal research data on A. marmelos phytochemical properties and pharmacological effects. This study aimed to explore the phytoconstituents, cytotoxicity, glucose uptake, and antioxidant and antidiabetic potential of an alcoholic extract of A. marmelos leaf. The cytotoxicity of A. marmelos in HepG2 cells was tested in vitro, and the results revealed that it has strong cytocompatibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…The hypoglycemic activities have been associated with marked antioxidant effects including a decrease in oxidative stress that manifested as a decrease in lipid peroxidation, an increase in the activity of cellular antioxidant mechanisms [128][129][130], and the regeneration of pancreatic β-cells [126]. These observations are in accordance with the notable antioxidant activity of A. marmelos leaf extracts in a DPPH free radicalscavenging assay and a ferric reducing antioxidant power assay [131,132] as well as in HepG2 cells cultured under glucose-rich conditions [132].…”
Section: Scientific Studies Have Validated Many Of the Ethnomedical U...mentioning
confidence: 68%
“…The hypoglycemic activities have been associated with marked antioxidant effects including a decrease in oxidative stress that manifested as a decrease in lipid peroxidation, an increase in the activity of cellular antioxidant mechanisms [128][129][130], and the regeneration of pancreatic β-cells [126]. These observations are in accordance with the notable antioxidant activity of A. marmelos leaf extracts in a DPPH free radicalscavenging assay and a ferric reducing antioxidant power assay [131,132] as well as in HepG2 cells cultured under glucose-rich conditions [132].…”
Section: Scientific Studies Have Validated Many Of the Ethnomedical U...mentioning
confidence: 68%
“…The physiologically active essential oils produced by the Rutaceae family are widely known and found in many family members, as well as its ornamental and culinary herbs, which include orange, lime, lemon, grapes, and satinwood [ 8 ]. Several studies have found various plant substances, including alkaloids, terpenoids, flavonoids and coumarins [ 9 ]. Plants in the Rutaceae family contain high amounts of coumarins, like Marmelosin and Luvangetin, which have antihelminthic, antiulcer, antibacterial and antispasmodic activity.…”
Section: Rutaceae Familymentioning
confidence: 99%
“…The alcoholic extract of A. marmelos leaves significantly inhibited the enzymes α-amylase and α-glycosidase with IC 50 values of 46.21 and 42.07 μg/ml, respectively. A. marmelos significantly reduced ROS levels that were elevated due to high glucose and enhanced glucose consumption in HepG2 cells (p < 0.05) [ 9 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The development of hypoglycemic medications, diabetes, and its associated consequences continue to be a significant concern in medicine. Diabetes can be managed with the help of several medicinal plants [ 156 , 157 ]. A study found that P. kurroa extract could eliminate oxygen free radicals such as superoxides and hydroxyl radicals and stop lipid peroxidation in rat liver homogenate caused by the Fe 2+ ascorbate system [ 158 ].…”
Section: Classical and Clinical Use Of P Kurroamentioning
confidence: 99%